Educational TIPS as a reminder method in compliance with the healthy self-care of elderly persons - Rojas-Bravo, Violeta (2020)
Objective. To demonstrate the effectiveness of educational tips as a reminder method in fulfilling healthy self-care of elderly persons (EP). Methods. The study was longitudinal, prospective and with intervention: before-after developed in 20 EP, belonging to the program of the Centro Integral del Adulto Mayor (CIAM) or Comprehensive Center for the Elderly of Municipality of Pillcomarca, in the province of Huanuco, Peru, during the year 2018. An interview guide of general characteristics of the sample and a questionnaire of compliance with healthy self-care was applied. Counseling sessions were developed using the educational tips through home visits. Student's t-test was used for related samples, in order to contrast the hypotheses and the bioethical principles were taken into account. Results. Regarding the analysis of compliance with healthy self-care of EP, it was found that, before the intervention, 35 % (7) had correct knowledge of healthy self-care. While, after it, 95% (19) achieved correct knowledge [t = -5.50; p = 0.00]. When contrasting the effectiveness of educational tips as a reminder method in the fulfillment of healthy self-care of EP, during the moments of the study, it was evident that, before the application of the tips, 30% (6) complied with healthy self-care. While, after the intervention, it increased to 85% (17). Conclusion.The intervention developed through educational tips as a reminder method is effective in fulfilling healthy self-care.